The mycoherbicide Atlernaria cassiae infects and alters phenolic metabolism of Cassia alata seedlings - Hoagland, R.E. (Phytoprotection, 1995)
The mycoherbicide Alternaria cassiae, a pathogen of the weed sicklepod (Cassia obtusifolia), was found to infect a previously untested Cassia species, Cassia alata (ringworm bush or seven golden candlesticks). When 2-wk-old, growth chamber-grown C. alata seedlings were inoculated with 105 spores mL-1 followed by a 12-h dew period, infection was apparent 16-20 h after treatment. Infection severity was proportional to spore concentration, and 106 spores mL-1 caused complete mortality 4-5 d after treatment. Plant age was also a factor in disease severity and mycoherbicidal efficacy. At 106 spores mL-1, 95% of 1- to 3-wk-old seedlings were killed (with severe damage to others); 3- to 4-wk-old plants had multiple lesions, growth reduction, and some leaf abscission; and 5- to 7-wk-old plants were infected with many lesions, but they outgrew these effects. Extractable phenylalanine ammonialyase in treated C. alata seedlings was increased three-fold above that of untreated seedlings 17-96 h after spore application. Soluble hydroxyphenolic levels were also increased in the A. cassiae-treated seedlings, but not until 48-96 h after treatment. Results indicate an expanded host range for this plant pathogen and suggest that phenolic metabolism is increased in défense of pathogen invasion.